THE INFLUENCE OF PRODUCT VALUE DURING THE PROCESS OF PURCHASE DECISION - Nicoleta CRISTACHE; Irina SUSANU; Sofia DAVID (Management & Marketing, 2008)
The success of the organisational actions is ensured by the permanentdialogue that is hold with the consumer in order to know and anticipate hisneeds and desires, in order to satisfy them better through the offered goodsand services. Found in the face of a polyvalent consumer, the marketingspecialists of the companies are provoked to find new landmarks in order tounderstand the mechanisms that guide the behaviour and to highlight theconsumers’ profile. Regarding the respect that must be granted to theconsumer, this begins with a real knowledge and understanding of theelements that are the basis of his decisions, respectively of the forming of hisbehaviour. Nowadays consumer is permanently searching for a direction thatis not always compatible with the notion of rationality or utility.